2017
DOI: 10.5860/crl.78.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Use of Author Identifiers and Researcher Networking Tools

Abstract: This cross-sectional survey focused on faculty use and knowledge of author identifiers and researcher networking systems, and professional use of social media, at a large state university. Results from 296 completed faculty surveys representing all disciplines (9.3% response rate) show low levels of awareness and variable resource preferences. The most utilized author identifier was ORCID while ResearchGate, LinkedIn, and Google Scholar were the top profiling systems. Faculty also reported some professional us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The presence of researchers on the four sites grouped by scientific disciplines (i.e. STM or HSS) is presented in Fig 1. As previously described, our data show that HSS researchers are over-represented on Academia.edu [17,27], whereas STM researchers were over-represented on ResearchGate [7,17,18,23,38]. However, regardless of the fact that ORCID and ResearcherID are not known to be specifically dedicated to HSS or STM, STM researchers were over-represented on them.…”
Section: Number Of Profiles By Scientific Disciplinessupporting
confidence: 70%
See 2 more Smart Citations
“…The presence of researchers on the four sites grouped by scientific disciplines (i.e. STM or HSS) is presented in Fig 1. As previously described, our data show that HSS researchers are over-represented on Academia.edu [17,27], whereas STM researchers were over-represented on ResearchGate [7,17,18,23,38]. However, regardless of the fact that ORCID and ResearcherID are not known to be specifically dedicated to HSS or STM, STM researchers were over-represented on them.…”
Section: Number Of Profiles By Scientific Disciplinessupporting
confidence: 70%
“…Indeed, difficulties encountered in tracking scholarly and institutional publications are numerous due to identical or similar names, name changes over time due to marriage, or the use of aliases or author groups [6]. Change of researcher affiliations over time, due to researcher mobility and/or lack of uniformity when declaring affiliations in articles are also well known difficulties [7,8]. Different spellings of names can occur due to alternative transliterations of some author names from other alphabets (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted that, although ORCID is a relatively new profile platform, 29% of the researchers had established a profile on this platform, a rate much higher than the rate of 3-15% reported in previous literature (Mikki et al 2015;Tran & Lyon 2017). In recent years, many efforts have been made to promote ORCID.…”
Section: Discussionmentioning
confidence: 99%
“…They found that while 37% of the researchers had at least one profile, ResearchGate was the most popular site (30%), followed by Google Scholar Citations (8%), while Academia.edu and ORCID only had 4% and 3% presence, respectively. In another study, Tran and Lyon (2017) surveyed the use of APWs in a US research university and found low levels of awareness of these resources. In terms of popularity of the profile websites, they found that the most used ones included ResearchGate (64%), Google Scholar Citations (54%), Academia.edu (24%), and ORCID (15%).…”
mentioning
confidence: 99%